2023
DOI: 10.1161/jaha.122.026466
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Balloon Pulmonary Angioplasty for Patients With Chronic Thromboembolic Pulmonary Hypertension and Comorbid Chronic Obstructive Pulmonary Disease

Abstract: Background Balloon pulmonary angioplasty (BPA) is a promising treatment modality for nonoperable chronic thromboembolic pulmonary hypertension (CTEPH). However, BPA for atypical CTEPH with concurrent chronic obstructive pulmonary disease (COPD) remains controversial owing to the risk of exacerbation of ventilation‐perfusion mismatch. We aimed to evaluate the efficacy and safety of BPA for CTEPH with moderate or severe COPD. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
1
1
Order By: Relevance
“…However, the efficacy of interventional treatment for CTEPH with pulmonary comorbidity had not been well studied. In contrast with previous studies [35] , our data did not show any changes in PFT parameters in patients with a pulmonary comorbidity. These discrepancies might partly be explained by the inclusion criteria used for the study population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy of interventional treatment for CTEPH with pulmonary comorbidity had not been well studied. In contrast with previous studies [35] , our data did not show any changes in PFT parameters in patients with a pulmonary comorbidity. These discrepancies might partly be explained by the inclusion criteria used for the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, significant improvements in hemodynamics were seen in CTEPH patients both with and without concomitant pulmonary pathology after BPA treatment, which is consistent with the findings of the study by Fujii et al [35] . Additionally, we found that right heart function was improved to varying degrees in both groups, whereas exercise capacity was improved only in CTEPH patients without underlying pulmonary disease.…”
Section: Discussionsupporting
confidence: 93%
“…In this issue of the Journal of the American Heart Association ( JAHA ), Fujii et al report on 32 patients with chronic obstructive pulmonary disease (COPD) undergoing balloon pulmonary angioplasty (BPA) for chronic thromboembolic pulmonary hypertension (CTEPH). 1 Patients were identified from a larger cohort of 149 patients with CTEPH who underwent BPA over a 10‐year‐period. COPD was diagnosed based on pulmonary function tests (forced expiratory volume in 1 s [FEV1]/forced vital capacity <70% and FEV1<80% predicted).…”
mentioning
confidence: 99%